DISAIN ALAT PENEPAT PENGELASAN KIT PEMADAM KEBAKARAN - Wilza, Romi; Novarika, Wirda; Rasid, M.; Herlambang, Yusuf Dewantoro; Arifin, Fatahul; Ikbal, Muhammad; Hadi, Kms. M. (AUSTENIT, 2022)
Fire is a disaster that no one wants. Fires can occur anytime and anywhere, one of which is offices, buildings, warehouses, and even forests. Fires in buildings can cause losses in both material and non-material properties. To extinguish the fire, you need supporting equipment, for example a Fire Extinguisher Kit (FEK), which is a fire hose reel. To produce this tool, a production aid is needed in terms of gripping the workpiece that will be used as a fire fighting kit product. Fire Hose Reel production aids are production workpiece holder tools that are used in order to make accurate doubling of components to get good work results in production, of course there should be compatibility in terms of the position of the workpiece with the machine used. The fixing device is used which is designed to position, hold, and support each part so every welding performed is within the specified limits. In the process of designing and manufacturing, this Welding Tool for Production of FEK uses software to calculate the load that these production aids can withstand and for the manufacturing process tools such as cutting grinders, drilling machines and other bench work tools are used. This tool can withstand the weight of objects up to 50 kg. with a deflection of 0.055 mm.